2018
DOI: 10.1007/s11892-018-1083-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Progression and Severity of Type 1 Diabetes: Potential Effects on Disease Mechanisms

Abstract: Purpose of review:To explore the impact of age on type 1 diabetes (T1D) pathogenesis. Recent findings:Children progress more rapidly from autoantibody positivity to T1D and have lower C-peptide levels compared to adults. In histological analysis of post-mortem pancreata, younger age of diagnosis is associated with reduced numbers of insulin containing islets and a hyper-immune CD20 hi infiltrate. Compared to adults, children exhibit decreased immune regulatory function and increased engagement and trafficking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 79 publications
0
31
0
Order By: Relevance
“…Genetics may provide a useful window into the puzzling age differences in the epidemiology, clinical characteristics, immunology, and histopathology of type 1 diabetes (12). Most of the genes that Inshaw et al (7) found preferentially associated with earlychildhood type 1 diabetes work in the immune system (13) (Fig.…”
mentioning
confidence: 99%
“…Genetics may provide a useful window into the puzzling age differences in the epidemiology, clinical characteristics, immunology, and histopathology of type 1 diabetes (12). Most of the genes that Inshaw et al (7) found preferentially associated with earlychildhood type 1 diabetes work in the immune system (13) (Fig.…”
mentioning
confidence: 99%
“…A unifying picture is emerging that prompts us to consider type 1 diabetes as a disease of both the immune system and beta cells, resulting from a conflicting dialogue between these two players. Given the phenotypic heterogeneity of type 1 diabetes, different phenotypic subtypes (endotypes) of islet autoimmunity are increasingly recognised based on putative pathogenic mechanisms and, likely, different responsiveness to immunotherapy ('theratypes') [60,61]. It is conceivable that distinct endotypes may also exist according to the aggressiveness of islet autoimmunity (benign vs progressive) and to the relative contribution of immune and beta cell drivers to such aggressiveness (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the two patterns of insulitis may reflect different degrees of severity, since patients with higher proportion of CD20 + B cells lose β‐cells at a more rapid rate . Therefore, higher proportions of B cells in insulitic lesions potentially represent a marker of an early aggressiveness of the autoimmune process or of a rapid rate of β‐cell loss …”
Section: Insulitis β‐Cell Loss and β‐Cell Persistence In T1dmentioning
confidence: 99%